2016
DOI: 10.1371/journal.pone.0158442
|View full text |Cite
|
Sign up to set email alerts
|

Kin Recognition in a Clonal Fish, Poecilia formosa

Abstract: Relatedness strongly influences social behaviors in a wide variety of species. For most species, the highest typical degree of relatedness is between full siblings with 50% shared genes. However, this is poorly understood in species with unusually high relatedness between individuals: clonal organisms. Although there has been some investigation into clonal invertebrates and yeast, nothing is known about kin selection in clonal vertebrates. We show that a clonal fish, the Amazon molly (Poecilia formosa), can di… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
34
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 48 publications
2
34
0
Order By: Relevance
“…These social fish form large groups in the wild where they forage and compete for resources together (Ingo Schlupp, Parzefall, & Schartl, 2002). These fish also strongly prefer to associate with familiar individuals (Makowicz, Tiedemann, Steele, & Schlupp, 2016; Ingo Schlupp, 2009); however it is currently unknown how the level of familiarity within a group influences group behaviour.…”
Section: Introductionmentioning
confidence: 99%
“…These social fish form large groups in the wild where they forage and compete for resources together (Ingo Schlupp, Parzefall, & Schartl, 2002). These fish also strongly prefer to associate with familiar individuals (Makowicz, Tiedemann, Steele, & Schlupp, 2016; Ingo Schlupp, 2009); however it is currently unknown how the level of familiarity within a group influences group behaviour.…”
Section: Introductionmentioning
confidence: 99%
“…Chemical information alone appears ineffective, although it is otherwise used widely in swordtails and other Poeciliids (Fisher & Rosenthal, ; McLennan & Ryan, ; Wong et al., ). We do not think that the method used here led to the lack of response, because in a different study using similar containers and investigating clonal recognition in the Amazon molly, females were able to recognize kin using all modalities investigated here (Makowicz et al., ). This strong role of visual communication is not a completely unexpected result, as visual displays are known to be important in swordtails, both in male contests and for acquiring mates.…”
Section: Discussionmentioning
confidence: 90%
“…Data were then normalized using √arc (sin) transformation. Any trials in which the female showed a side bias (more than 85% of time on one side; McCoy et al, 2011;Makowicz et al, 2016) were excluded from analysis. Eighteen trials were excluded due to side bias, but a binomial test indicated that side biases were distributed randomly between the two sides.…”
Section: Study 2: Dummy Testmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has shown that there is an association between codon usage and the evolutionary age of genes in metazoans 30 . Interestingly, two principal component analyses (PCA) of relative synonymous codon usage (RSCU) from 82 and 76 species (six species having distant codon usage patterns were excluded), respectively, revealed that the whale shark pattern of RSCU is most similar to that of the coelacanth; with well separated patterns of RSCU for each class (Fig.…”
mentioning
confidence: 96%